Household Economies of Chepang People in Chitwan - Sharma, Ganesh; Aryal, Badri (Economic Literature, 2018)
This study attempts to characterize a typical Chepang community in Chitwan district with reference to their economy at household level based on the study conducted in Lothar Village Development Committee. Chepang are considered to be one of the highly marginalized communities in Nepal having traditional subsistence based small economies. Their houses are small with mud floor, stone walls and straw roofs. One third of the Chepang households do not have toilets. They rear small number of mixed livestocks in a house eg. Cattle, buffaloes, poultry, goat and pig. They do not have household amenities like freeze, telephone, television, computer, motorcar and motorbike; but have mobile phones. More than ninty percent of Chepang go to jungle to collect one or the other types of edibles like githavyakur, wild fruits, and chiuri.Ninty five percent of Chepang people do not have bank account, thus rely on their friends and relatives for borrowing in household needs for money. Chi-square test reveals highly significant association between size of landholding and food sufficiency months, level of education and annual income, purpose of taking loan and sources of loan; as well as estimated annual income and account holding in bank. Economic Literature, Vol. XIII August 2016, page 39-45